Glucose Metabolites Exert Opposing Roles in Tumor Chemoresistance - Huang, Chung-Yen; Huang, Ching-Ying; Pai, Yu-Chen; Lin, Been-Ren; Lee, Tsung-Chun; Liang, Pi-Hui; Yu, Linda Chia-Hui (Frontiers in Oncology, 2019)
Reprogrammed glucose metabolism and increased glycolysis have been implicated in tumor chemoresistance. The aim was to investigate the distinct roles of the glucose metabolites pyruvate and ATP in chemoresistance mechanisms, including cell death and proliferation. Our data showed higher glucose transporters in colorectal cancer (CRC) from nonresponsive patients than those responsive to chemotherapy. Human CRC cell lines exposed to 5-fluorouracil (5-FU) displayed elevated cell viability and larger tumors in xenograft mouse models if cultured in high-glucose medium. Glucose conferred resistance to 5-FU-induced necroptosis via pyruvate scavenging of mitochondrial free radicals, whereas ATP replenishment had no effect on cell death. Glucose attenuated the 5-FU-induced G0/G1 shift but not the S phase arrest. Opposing effects were observed by glucose metabolites; ATP increased while pyruvate decreased the G0/G1 shift. Lastly, 5-FU-induced tumor spheroid destruction was prevented by glucose and pyruvate, but not by ATP. Our finding argues against ATP as the main effector for glucose-mediated chemoresistance and supports a key role of glycolytic pyruvate as an antioxidant for dual modes of action: necroptosis reduction and a cell cycle shift to a quiescent state.